PERAN GURU KELAS TERHADAP PEMBENTUKAN KEPRIBADIAN SISWA MELALUI PENERAPAN NILAINILAI KARAKTER PANCASILA DI SDN 3 KEBUTUHDUWUR KECAMATAN PAGEDONAGAN, BANJARNEGARA - Dwi Nartati; Ana Andriani (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2021)
This research is motivated by a phenomenon that the values of Pancasila character in schools are starting to fade. Evidenced by the many cases of juvenile delinquency, student bullying, lack of discipline and responsibility, and drugs. Schools as educational institutions are expected to be agents of change for students. The teacher is a figure who is always digested and imitated by students. The role of the teacher as a role model and motivator has a big role in student reception. The results of the study proved that there was an improvement in conditions before and after the study. These objectives are: (1) To describe the role of classroom teachers in student personality research at SDN 3 Kebutuhduwur, Pagedongan District, Banjarnegara. (2) To describe how to apply the values of Pancasila characters to personality traits in SDN 3 Kebutuhduwur, Pagedongan District, Banjarnegara. The method used is descriptive qualitative. The results show that the role of classroom teachers in the application of the character values of Pancasila can increase the sense of discipline and responsibility towards their duties.